Secondary mania due to AIDS and cryptococcal meningitis in a 78‐year‐old patient. Issue 2 (27th April 2015) - Chou, Po‐Han; Ouyang, Wen‐Chen; Lan, Tsuo‐Hung; Chan, Chin‐Hong
Abstract: We report a 78‐year‐old man without past psychiatric history who experienced his first manic episode successfully treated with quetiapine and lorazepam, but was ultimately found to have AIDS and Cryptococcus neoformans meningitis. Our presented case highlights the importance of comprehensive differential diagnoses to rule out secondary causes of psychiatric symptoms presenting for the first time in elderly patients.